POST-SOCIALIST TRANSFORMATION OF IZMAIL PUBLIC SPACE OF ODESSA REGION: PROBLEMS AND PERSPECTIVES (City: History, Culture, Society, 2023)
The problems and prospects of Izmail’s post-Soviet public space transformation are investigated. Publications on local news websites and Facebook, as well as official documentation from local authorities, were the primary sources. The development stages of the Izmail spatial structure are described. The final phase is characterized by a combination of partial deindustrialization, commercialization, and democratization of public space. Despite significant progress over the past three decades, Izmail’s urban public space is plagued by a multitude of issues. First, the sites of former large Soviet industrial enterprises, such as the Etalon plant, have not been revitalized. Second, automobile traffic was prioritized in transport development, thereby diminishing the potential of Izmail’s public space. Thirdly, lack of public space accessibility for people with disabilities. Lack of respect for the town’s historical heritage is the fourth issue. Inaction on the part of the local government and inactivity on the part of the city’s residents are the primary causes and aggravators of these problems. A positive trend is the alteration of the space’s symbolic filling: decommunization and an increase in the representation of Ukrainian national and religious symbols.
Keywords: Izmail; urban space; public space; post-socialist transformation